The Effect of SHRM Practices on Innovation Performance: The Mediating Role of Global Capabilities - Zehir, Cemal; Uzmez, Ahmet; Yildiz, Hacer (ELSEVIER SCIENCE BV, 2016)
The relationship between strategic human resources management (SHRM) practices and innovation performance is one of the main topics that has been examined recently. However, there are very few studies investigating the role of some specific capabilities which an organization must have, on this relationships. For this reason, this study tries to figure out the mediator effect of global capabilities on the relationship between SHRM practices and innovation performance. For this paper, data is collected through a questionnaire from the managers of four Islamic Banks which are operating in Turkey. Analyzes are done by using SPSS statistics software and AMOS program. According to the results, SHRM practices influence innovation performance in a positive way and global capabilities have a mediator effect on this relationship. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: SHRM Practices; Innovation Performance; Global Capability; Islamic Banking; HUMAN-RESOURCE MANAGEMENT; FIRM PERFORMANCE; MANUFACTURING PERFORMANCE; IMPACT; PRODUCTIVITY; SYSTEMS; HRM; Business & Economics